2021
DOI: 10.1021/acsnano.0c10121
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Coupling-Stabilized Transition-Metal Sulfide/Carbon Nanotube Composites for Lithium/Sodium-Ion Batteries

Abstract: Transition-metal sulfides (TMSs) powered by conversion and/or alloying reactions are considered to be promising anode materials for advanced lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs). However, the limited electronic conductivity and large volume expansion severely hinder their practical application. Herein, we report a covalent coupling strategy for TMS-based anode materials using amide linkages to bind TMSs and carbon nanotubes (CNTs). In the synthesis, the thiourea acts as not only the cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 66 publications
3
62
0
Order By: Relevance
“…[ 20 ] In the NSCs, the peaks in both the Sn 3d and S 2p spectra shifted to a higher binding energy when compared with the bare SnS samples, meaning that electrons transferred from the SnS to the carbon layers. [ 31,33,44–46 ] Interestingly, it was found that the VA‐SnS@C exhibited significantly larger shifts of the peaks in both spectra when compared to the PL‐SnS@C. This suggests that more electrons transferred to the carbon layers in the VA‐SnS@C, which is consistent with the Raman spectral observations. Moreover, new shoulder peaks at 163.71, 165.12, and 285.79 eV were observed in the S 2p and C 1s spectra for both NSC samples, which could be attributed to CS bond formation.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…[ 20 ] In the NSCs, the peaks in both the Sn 3d and S 2p spectra shifted to a higher binding energy when compared with the bare SnS samples, meaning that electrons transferred from the SnS to the carbon layers. [ 31,33,44–46 ] Interestingly, it was found that the VA‐SnS@C exhibited significantly larger shifts of the peaks in both spectra when compared to the PL‐SnS@C. This suggests that more electrons transferred to the carbon layers in the VA‐SnS@C, which is consistent with the Raman spectral observations. Moreover, new shoulder peaks at 163.71, 165.12, and 285.79 eV were observed in the S 2p and C 1s spectra for both NSC samples, which could be attributed to CS bond formation.…”
Section: Resultssupporting
confidence: 70%
“…[ 23 ] The greater exposure of the open edges and defects then facilitates a strong electronic interaction with the carbon layers within the composite, which enhances the charge transfer kinetics and enriches the active sites, which is favorable for ion pseudocapacitance storage. [ 30,31 ] In addition, the strong interaction with the carbon layers enhances the structural stability by effectively suppressing electrode pulverization and particle agglomeration. [ 32,33 ] Therefore, to fully exploit the exceptional electrochemical properties of NSCs, it is important to fully understand the effect of the crystallographic orientation of SnS.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18,22 ] To address above issue, constructing a hybrid structure with carbon materials has been employed as an efficient strategy to improve the comprehensive performance of electrode materials. [ 14,23,24 ] In general, through careful design of nanostructures, carbon materials are endowed with good electronic conductivity and good elasticity. [ 23,25,26 ] Therefore, anchoring the active material onto the carbon matrix would not only largely enhance the reaction kinetics, but also alleviate structural damage and pulverization of the active material during K‐ions insertion or extraction, offering extra benefits for the cycling stability of the active materials.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14,23,24 ] In general, through careful design of nanostructures, carbon materials are endowed with good electronic conductivity and good elasticity. [ 23,25,26 ] Therefore, anchoring the active material onto the carbon matrix would not only largely enhance the reaction kinetics, but also alleviate structural damage and pulverization of the active material during K‐ions insertion or extraction, offering extra benefits for the cycling stability of the active materials. [ 15,22,27,28 ] Beyond carbon hybridization, the rationally structural engineering is another effective route for improving the K‐ions storage performance.…”
Section: Introductionmentioning
confidence: 99%
“…The observed increased capacity after 150 and 170 cycles at 500 and 1000 mA g –1 , respectively, can be attributed to the formation of a polymeric layer (Figure S15, Supporting Information) that was beneficial for surface capacity. [ 45–47 ] As such, the material showed a capacity of 510, 360, and 330 mA h g –1 after 700, 1200, and 2300 cycles at a current density of 200, 500, and 1000 mA g –1 , respectively. For comparison, the lithium storage performance of other Co‐based MOFs or COFs was listed in Table S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 96%